Estudo dos constituintes químicos dos resíduos madeireiros de Andira Parviflora, Dipteryx odorata e Swartzia laevicarpa (Fabaceae) - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
During wood processing by timber industry around 70% of lumber becomes unusable (garbage), which usually is thrown away at inappropriate places, causing environmental troubles. In attempt to assuage this problem and trying harnessing the underused waste, some proposals have been emerged, like the use of these residues to produce handcrafts which reduces the waste of wood and adds a great value to a thing that is seen as a trash. Other proposal is the present study, which proposed the phytochemical study of three timber species of Fabaceae family: Dipteryx odorata (cumaru), Swartzia laevicarpa (saboarana) e Andira parviflora (sucupira-vermelha), contributing for the knowledge of the chemical constituents of the wood, and in search for secondary metabolites with biological activity or chemical relevance. The organic crude extracts were fractionated by chromatography column (CC). The fractionation of the dichloromethane extract from residues of S. laevicarpa, resulted in the isolation of 8-hydroxy-3,4,9,10-tetramethoxipterocarpan. The methanolic extract of D. odorata fractionated in CC led the isolation of four isoflavones: 8-O-metilretusin, cladrastrin, 7,3’-dihydroxy-8,4’dimethoxi-isoflavone and the 7,3’-dihydroxy-5,6,4’-trimethoxi-isoflavone, this last one is reported for the first time. The fractionation of the methanolic extract of the alburnum of A. parviflora in CC led the isolation of the isoflavone genistein, and in the methanolic extract of A. parviflora's core were isolated the 7,5’,6’-trihydroxy-4’-methoxi-isoflavan and biochanin A. The resulting mother liquor of biochanin A, was evaluated by HPLC-EFS-NMR, leading to the isolation and identification of substances 3,8-dihydroxy-9-methoxipterocarpan,8-dihydroxy-9-methoxipterocarpan, nissolin, medicarpin, biochanin A and the novel bipterocarpan medicarpin secundiflorol-I (OC 3 → C-3 '). In this work were identified by spectroscopic techniques flavonoids (isoflavone, isoflavan and pterocarpan) typical of the Fabaceae family.
Keywords: Resíduos madeireiros; Isoflavonoides; CLAE-EFS-RMN; Wood waste; Isoflavonoids; CIÊNCIAS EXATAS E DA TERRA: QUÍMICA